2021
DOI: 10.3892/wasj.2021.123
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammatory and liver function markers in assessing the prognosis of patients with COVID‑19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused Coronavirus disease 2019 in early December, 2019. The disease begins as a respiratory disease with varied outcomes, from complete recovery to long-standing complications, such as respiratory distress, heart ailments and stroke. The present study was undertaken to identify the derangements in liver function and inflammatory status which may be used to diagnose the severity and thus assess the prognosis of patients with COVID-19 infection. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…Our investigation also indicated that COVID-19 patients showed markedly deviations in the concentrations of ferritin, LDH, AST, ALT, CK, pro-BNP, urea, and creatinine. This is in line with the results of previous studies that dealt with the diagnostic and prognostic value of laboratory findings in COVID-19 patients [ 8 , 47 , 48 ]. The aggrevated inflammatory response in SARS-CoV-2 infection causes multiorgan dysfunction that is reflected through a remarkable increase in different laboratory parameters.…”
Section: Discussionsupporting
confidence: 91%
“…Our investigation also indicated that COVID-19 patients showed markedly deviations in the concentrations of ferritin, LDH, AST, ALT, CK, pro-BNP, urea, and creatinine. This is in line with the results of previous studies that dealt with the diagnostic and prognostic value of laboratory findings in COVID-19 patients [ 8 , 47 , 48 ]. The aggrevated inflammatory response in SARS-CoV-2 infection causes multiorgan dysfunction that is reflected through a remarkable increase in different laboratory parameters.…”
Section: Discussionsupporting
confidence: 91%
“…White blood cell and neutrophil counts were observed to be significantly greater in individuals with increased ALT, and both indices had substantial positive relationships with aminotransferases [24]. Another study by Moorthy et al, there was negative correlation between liver function tests with the WBC [25]. Diaz et al research found that although the influence of lymphocytes on AST, ALP, and even ALT was lost toward the end of the study, the relationship between lymphocytes and AST, ALP, and even ALT remains robust [26].…”
Section: Discussionmentioning
confidence: 89%
“…On the other side, the increase of 1 MPV unit between the first and third days during treatment is inseparable from thrombocytopenia, which is experienced by 58-95% of severe cases of COVID-19 and increased by 1.76 times the risk of mortality [24,25]. Then significantly increased NLRs are also commonly found in patients treated in intensive care units with severe disease, with each unit increase in NLR associated with an 8% increase in the risk of death from COVID-19 [10,26].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation increases capillary permeability and albumin transfer to extracellular, so albumin levels tend to decrease as a marker of endothelial damage [8,9]. Cytokine storm conditions will reduce lymphocyte production in the bone marrow and increase the use of lymphocytes and neutrophil production as an inflammatory response increasing the neutrophil-lymphocyte ratio (NLR) [7,10,11]. In addition, a cytokine storm will cause coagulation abnormalities and thrombus formation, characterized by an increase in the mean platelet volume (MPV) as a reflection of pro-inflammatory and prothrombotic [7,12].…”
Section: Introductionmentioning
confidence: 99%